Mutu Pendidikan Sekolah Dasar di Kabupaten Kutai Timur - Hasanah, Siti Nur (SYAMIL: Journal of Islamic Education, 2017)
This research is motivated by the quality of education in East Kutai District. It was not equally between infrastructure and suprastructure school developments in the rural and the urban areas. It also can be effect to the quality of educations in East Kutai District, especially in rural areas. The aims of this research are describes the quality condition of elementary schools in East Kutai District, discribes supporting factors and obstacle factors, and the efforts of goverment (ministry of education) to improve the quality education  of elementary schools in East Kutai District.This is descriptive qualitative research. It was located in education goverment office (ministry of education).The result of this research was indicated that the quality education of elementary school in East Kutai Distric is excellent. It shows from the increase accreditation result every year. At 2016 all of elementary schools in East Kutai District was accredited. It was good progress. Eight national education standarts have been achieved. The supporting factors to increase the quality education of elementary school in East Kutai District, such us:  qualified human resources, a lot of budget funds, between elementary schools and ministry of education has been mutual support, good infrastructure development, and good geographic location. Even while obstacle factors such us: small budget funds, the school locations are so far from the town, education policies always change every a new minister education, and different understanding about education mindset. The efforts from education department goverment (ministry of education)  to improve the quality education of elementary school in East Kutai District are: complete the database, reorganized institution, change mindset the teachers from teachers become educators, make a program training and coaching, adjusting teacher qualifications,  make a program one sub district one favorite school, make a curriculum development, strengthening of character education, make a programe one student one book of curriculum 2013, make a mapping and dissemination for all teachers, rolling teachers and head master, make a program rehabilitation of all facilities and infrastructure, do controling from UPT.